Pengaruh Pendampingan oleh Penyintas Kanker Terhadap Motivasi Pasien Kanker Payudara dalam Menjalani Pengobatan - Mumpuni Mumpuni; Fenti Hasnani (Jurnal Health Sains, 2023)
Cancer patients must be accompanied so that long struggles do not occur which result in delayed therapy. This study aims to determine the effect of assistance by cancer survivors on motivation to undergo treatment in cancer patients. This research is a quantitative study with a quasi-experimental method with the Control Group Post test only design approach or the post test control group. The research was conducted at the Indonesian Breast Cancer Foundation Halfway House and Dharmais Hospital Jakarta. The sample consisted of 64 people which were divided into 32 people in the control group and 32 people in the intervention group. The intervention provided is assistance by survivors. Data is collected through a questionnaire. Based on the Mann Whitney Test, a significance value of 0.000 <0.05 was obtained, meaning that there were differences in the motivation of breast cancer patients in the group that received assistance and the group that did not receive assistance. So it was concluded that assistance by breast cancer survivors affects the motivation of breast cancer patients. This can be supported by the descriptive test that was carried out earlier that the motivation of the cancer patients in the assisted group obtained a higher average value than the group who did not receive assistance.